Total Volatile Base, Glycogen, Cathepsin, and Water Holding Capacity of Tilapia (Oreochromis niloticus) on Deteoritation Phase - Suhandana, Made; Nurhayati, Tati (Marinade, 2018)
Fish was a highly perishable product. The deterioration of fish quality was followed by modification of biochemical components. These Biochemical components include a total volatile base, glycogen, cathepsin activity, and water holding capacity. The objective of this study was to determine the changes of biochemical components in fish deterioration quality. The highest TVB value showed on post rigor phase (38,40 mg N/100 g). The highest glycogen content showed on pre-rigor phase (765,1707 mg/ml). The decreasing of cathepsin activity showed on rigor mortis until post rigor phase, 0,0285 U/ml to 0,0095 U/ml. The ability fresh fish to retain water (76,39%) from total moisture content (76,89%).